Critical Appraisal of Pharmaceutical Therapy in Diabetic Cardiomyopathy—Challenges and Prospectives - Elina Khattab; Michaelia Kyriakou; Elena Leonidou; Stefanos Sokratous; Angeliki Mouzarou; Michael M. Myrianthefs; Nikolaos P. E. Kadoglou (Pharmaceuticals)
Diabetes mellitus (DM) is a multifaceted disorder with a pandemic spread and a remarkable burden of cardiovascular mortality and morbidity. Diabetic cardiomyopathy (DBCM) has been increasingly recognized as the development of cardiac dysfunction, which is accompanied by heart failure (HF) symptoms in the absence of obvious reasons like ischemic heart disease, hypertension, or valvulopathies. Several pathophysiological mechanisms have been proposed, including metabolic disorders (e.g., glycation products), oxidative stress, low-grade inflammation, mitochondrial dysfunction, etc., which should guide the development of new therapeutic strategies. Up to now, HF treatment has not differed between patients with and without diabetes, which limits the expected benefits despite the high cardiovascular risk in the former group. However, DBCM patients may require different management, which prioritize anti-diabetic medications or testing other novel therapies. This review aims to appraise the challenges and prospectives of the individualized pharmaceutical therapy for DBCM.